Eksistensi Tari Batin Kemuning Di Kecamatan Tembilahan - Zulmi Irvanda; Susmiarti Susmiarti (SENDRATASIK UNP, 2021)
This study aims to describe and analyze the existence of the Batin Kemuning Dance in Tembilahan District. This type of research is a qualitative research with a descriptive analysis method. The main instrument in this study is the researcher himself and is assisted by supporting instruments such as writing instruments and cameras. The data collection technique is done by means of literature study, observation, interview and documentation. The steps in analyzing data are collecting data, presenting data, drawing conclusions. The results showed that the Batin Kemuning Dance is a Malay creation dance created to participate in the 2007 Nusantara Dance Parade at Sanggar Sri Gemilang, Tembilahan District. In 2008-2010, Batin Kemuning Dance was always used at events organized by the Tourism, Youth, Sports and Culture Office (DISPARPORABUD) of Indragiri Hilir Regency to perform inside, outside the region to foreign countries. In 2011-2013, Batin Kemuning Dance experienced a decline because Sanggar Sri Gemilang tried to perform another dance, but in this span of this year, the Batin Kemuning Dance actually developed on social media (Youtube). In 2014-2019, Batin Kemuning Dance was always used again at government events managed by DISPARPORABUD. In 2020 the Batin Kemuning Dance was not performed due to the Covid-19 virus outbreak where all events were canceled.